DARI IDEOLOGI KE STRUKTUR KELEMBAGAAN: Studi Keterlibatan Muslim (Ortodok) dan Penghayat Kebatinan Purwa Ayu Mardi Utama dalam Struktur Kelembagaan Desa Kemiren Kabupaten Banyuwangi - MASRIFA, LIA HILYATUL ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This study is intended to examine about the struggle between the Muslim community (Orthodox) and psychotherapy pengahayat Kemiren PAMU in East Java. Historically, the background of different beliefs and ideologies influence both in getting involved in the institutional structure. Using qualitative methods of descriptive-analytic phenomenology of religion, the researcher examines religious phenomena related to ideology, the struggle for religious influence in society, social, economic and political. Using the concept of Ideological State apartus Althusser, certain elites began to include ideology on the institutions such as religion, education, family and other legal instruments. In the long seajarah Kemiren between psychotherapy penghayat PAMU (purwa Ayu Main Mardi) and Muslims form a socio-political stream in the village structure. Briefly, that the presence of different ideologies capable of splitting political sectors between the two. Institutional structure used as an arena of contestation ideology by both. In primary education, school policies supported by the village kebijkaan require for their students to be able to read the Koran and women employees and teachers are encouraged to use the hijab during working hours, ideologically invested early on in education will be more effective and teachers provide learning about religion Islam formally and looks more positive. And PAMU involve themselves in the customs and institutions have an important influence in this local institution, such as when the customs and religious rituals they portray themselves with the ideology of the existence of the trust to actualize PAMU. Karapkali we know that Islam has a strong legitimacy both vertically (government) and horinsontal (social) able to divert local beliefs that minority. PAMU that bureaucracy is not recognized as a religion using a horizontal approach to bridge the gap caused by religious factors or culture so as to reduce the gap caused by these factors. Keywords: Ideology, Religion, Village Government, Indigenous Institute, penghayat Kebatinan (PAMU), Muslims (Orthodox)